The Impact of Ideological Radicalization on the Social and Psychological Well-being of Adolescents - Reiner, Amoz Defreda (IHSA Institute, 2025)
This research investigates the impact of ideological radicalization on the social and psychological well-being of adolescents. The primary objective is to understand how exposure to extremist ideologies influences adolescents' emotional health, social relationships, and identity development. The research design incorporates a mixed-methods approach, combining quantitative surveys with qualitative interviews to gather data from adolescents in various communities. The methodology involves analyzing the psychological and social effects of radicalization, identifying risk factors, and exploring the effectiveness of existing preventive and intervention strategies. The main outcomes reveal that ideological radicalization contributes significantly to emotional distress, anxiety, depression, and social isolation among adolescents. Results also highlight the importance of early detection, the role of critical thinking education, and the need for mental health support and rehabilitation programs to address radicalization. In conclusion, the study emphasizes the need for a comprehensive approach involving educators, mental health professionals, and policymakers to prevent radicalization and promote adolescent well-being, ensuring a healthier, more resilient generation.